Training on Environmentally Friendly Science Media Creation for Elementary School Teachers - Hamna, Hamna; BK, Muh Khaerul Ummah; Fajrin, Moh; Aulia, Mirda (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This community service program was carried out as an effort to enhance the ability of elementary school teachers to design and develop creative, economical, and environmentally friendly science learning media. The program took place at SD Negeri Dadakitan 1, involving teachers and fifth-grade students as participants. The method employed was a qualitative descriptive approach consisting of three main stages: (1) initial observation and needs analysis of teachers regarding learning media, (2) implementation of training through material presentation, demonstration, and hands-on practice, and (3) reflection and evaluation of the program outcomes. The results indicated a significant improvement in teachers’ pedagogical competence, creativity, and environmental awareness after participating in the training. Teachers were able to utilize recycled materials such as plastic bottles, straws, and balloons to create innovative learning media for the topic of the respiratory system. The produced media were not only attractive and easy to make but also effective in helping students understand abstract science concepts through concrete learning experiences. Moreover, students showed high enthusiasm and active engagement during the learning process. Overall, this training program successfully promoted the development of innovative and eco-friendly learning media while fostering ecological awareness and sustainable behavior among both teachers and students.